Astroglia in neuropathology - Verkhratsky, Alexei (Henry Stewart Talks, 2011)
Reactive astrogliosis, Anisomorphic and isomorphic astrogliosis, Up-regulation of GFAP synthesis, Initiation and regulation of reactive astrogliosis, Neuroprotection and neurotoxicity, Alexander's disease, Astrocytes in ischaemia and stroke, Brain oedema, Possible neuroglial roots of neurodegeneration
Archived at 2022/03/31